2009
DOI: 10.4049/jimmunol.0802845
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Recognize and Kill Human Glioblastoma Cells with Stem Cell-Like Properties

Abstract: In this study, cancer cells were isolated from tumor specimens of nine glioblastoma patients. Glioblastoma cells, cultured under suitable culture conditions, displayed markers typical of neural stem cells, were capable of partial multilineage differentiation in vitro, and gave origin to infiltrating tumors when orthotopically injected in NOD/SCID mice. These cells, although resistant to freshly isolated NK cells, were highly susceptible to lysis mediated by both allogeneic and autologous IL-2 (or IL-15)-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
266
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 292 publications
(279 citation statements)
references
References 36 publications
12
266
1
Order By: Relevance
“…These observations are in agreement with those previously reported in other human solid tumor experimental systems. [15][16][17]25 In Fig. 2, NK cells were activated with IL2 in vitro, whereas autologous and allogeneic NK cells were used as effectors without any activation in Table 1.…”
Section: Tumorspheres Derived From the Murine Erbb2mentioning
confidence: 99%
See 2 more Smart Citations
“…These observations are in agreement with those previously reported in other human solid tumor experimental systems. [15][16][17]25 In Fig. 2, NK cells were activated with IL2 in vitro, whereas autologous and allogeneic NK cells were used as effectors without any activation in Table 1.…”
Section: Tumorspheres Derived From the Murine Erbb2mentioning
confidence: 99%
“…The low levels of MHC class I expression reported in CSCs hints at the low efficiency of CSC targeting by CD8 C T lymphocytes. 14,15 However, the expression of ligands for NK-activating receptors (NKG2D, NCR and DNAM-1) [15][16][17] points to NK cells and other innate immunity effector cells being able to recognize and eliminate CSCs. Indeed, recent data have demonstrated that human gd T cells can target CSCs in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an autologous setting, normal cells are spared from NK-mediated killing because of the expression of high (protective) amounts of self-HLA class I molecules and of the lack of (or low) expression of ligands for activating NK receptors. However, tumors become susceptible to killing mediated by autologous NK cells because of a defective (nonprotective) expression of HLA class I molecules and de novo expression or up-regulation of ligands for activating NK receptors (6,7,9,11,12).…”
mentioning
confidence: 99%
“…Different cellular ligands have been identified (5). DNAM-1 recognizes PVR and Nectin-2, two Nectin family members that are overexpressed in tumors (6,7), and NKG2D interacts with MICA/B and ULBP. 2B4 interacts with CD48, NKp80 recognizes the activationinduced C-type lectin (AICL) (8), and NTBA displays homophilic interaction.…”
mentioning
confidence: 99%